Walking behaviour of healthy elderly: attention should be paid - Schmidt André; de Bruin Eling D (Behavioral and Brain Functions, 2010)
Abstract Background Previous studies have reported an association between executive function (EF) and measures of gait, particularly among older adults. This study examined the relationship between specific components of executive functions and the relative dual task costs of gait (DTC) in community-dwelling non-demented older adults, aged 65 years and older. Methods Temporal (stride time, stride velocity) and spatial (stride length) gait characteristics were measured using a GAITRite®-System among 62 healthy community dwelling older adults while walking with and without backward counting (BC) at preferred and fast walking speeds. Specific executive functions divided attention, memory and inhibition were assessed using the Test for Attentional Performance (TAP). Other measures included Mini-Mental State Examination (MMSE), amount of daily medications taken, educational level and sociodemographic characteristics. Adjusted and unadjusted multivariable linear regression models were developed to assess the relations between variables. Results High relative DTC for stride time, stride velocity and stride length were associated with divided attention at fast walking speed. High relative DTC for stride time was associated with divided attention at preferred walking speed. The association between high DTC of stride length and memory was less robust and only observable at preferred walking speed. None of the gait measures was associated with inhibition. Conclusions Spatial and temporal dual task cost characteristics of gait are especially associated with divided attention in older adults. The results showed that the associated DTC differ by executive function and the nature of the task (preferred versus fast walking). Further research is warranted to determine whether improvement in divided attention translates to better performance on selected complex walking tasks.